Emotional Response and Behavioral Coping Associated with Experienced and Media Discrimination Among Asians and Asian Americans in the United States - Chiang, Pamela P. (Race and social problems, 2023)
This paper examined how sources (experienced and media) and forms (overt and subtle) of discrimination were associated with emotional response and behavioral coping among Asians and Asian Americans during the COVID-19 pandemic. Data were collected in June 2020 from 249 Asian and Asian American adults living in 20 U.S. states. We used hierarchical regression for data analysis, controlling for age, gender, and the length of residence in the U.S. Results showed that experienced discrimination, especially in the overt form, was associated with both emotional responses (i.e., emotional distress and vigilance) and behavioral coping (i.e., using avoidant behavior to protect oneself). Media discrimination was associated only with emotional response. The relationship between experienced discrimination and emotional response was less pronounced among those who frequently observed discrimination in the media. Notably, subtle discrimination through personal experience or media exposure was positively associated with behavioral coping. The results suggest the need to address the rising anti-Asian acts with more initiatives in policy and practice, with special attention paid to the parallel influences from personal experience and media exposure to violence.